New Matrix Domain Derived by the Matrix Product - Karakaya, Vatan; Simsek, Necip; Dogan, Kadri (UNIV NIS, FAC SCI MATH, 2016)
In this work, we define new sequence spaces by using the matrix obtained by product of factorable matrix and generalized difference matrix of order m. Afterward, we investigate topological structure which are completeness, AK-property, AD-property. Also, we compute the alpha-, beta- and gamma- duals, and obtain bases for these sequence spaces. Finally we give necessary and sufficient conditions on matrix transformation between these new sequence spaces and c, l(infinity).
Keywords: Generalized difference sequence space; generalized weighted mean; AK and AD properties; the alpha-, beta- and gamma- duals and bases of sequences; matrix mappings; PARANORMED SEQUENCE-SPACES; TOPOLOGICAL PROPERTIES; TRANSFORMATIONS; EULER; Mathematics